O poder da marca empregadora em situações de crise: estudo de caso em um hospital durante a pandemia Covid-19 - Sampaio, Priscila Aparecida Surita (2021)
The global covid-19 pandemic created a challenging environment in the People Management area and boosted meaningful changes to the corporate world. Health institutions had to deal with these changes, at the same time that, acted in the front line confronting the virus. The health institution that was researched reinforced the premise of person’s centered care, looking after security guidelines and the health of all its patients and employees. To support the demand of attendance, a specific contingency plan was structured, with the rise of 1.436 professionals, hirings realized in fifteen days in march of 2020. Considering the situation's complexity, a transformation process on human resources was necessary. The main objective of this study was to investigate the power of the employer brand in a crisis situation, through the use of Agile Approach on recruitment and selection at a private hospital. Specific objectives were i) analyze the impacts caused by the use of agile methods to recruit and select talents during the covid-19 pandemic; and ii) analyze the impacts of "pride in belonging" to the employees fidelity. For that, it was realized qualitative exploratory research, with deep interviews. Seven interviews were conducted with assistential professionals that worked on the front line of the pandemic and that, after the determined time period on the contingency plan, were hired and kept the employment relationship with the institution. It was possible to conclude that a fast capacity of transformation on the process of recruitment and selection, the development opportunity, and the feeling of "pride in belonging" boosted the engagement, and provided a better commitment and the desire of permanency, generating positive impact to the brand and influencing the workspace. Besides that, the study showed that implementing digital features to conduct the process of hiring boosted a rupture of paradigm on the process of recruitment and selection at hospitals. Public or private health institutions can benefit from the results shown in this study, to the construction of new business models utilizing Agile Approach or to the definition of strategies directed to potentialize actions referred to the positioning of the employing brand.